Polarization-controlled plasmonic structured illumination on metasurface platform - Wei, Xinzhi (Nanyang Technological University, 2022)
The application and development of optical microscopic imaging technology has greatly promoted people's research and cognition of life phenomena. Future high-performance wearable and portable optical devices and systems, especially camera systems with small size and light weight will require components with small form factor and enhanced functionality. Structured light illumination micro imaging technology (SIM) has made an incalculable contribution to the field of biomedical imaging because of its advantages including high-resolution, wide-field, and quick imaging capabilities. Applying plasmonic system in SIM has let imaging beyond diffraction limit. This paper has applied plasma generated from fish bone shaped metasurface. By doing the simulation on FDTD, verify that we can shift the structured plasmonic field by changing the polarization state of incident light.